(untitled) (Proceedings of International Educators Conference, 2024)
Rheumatism is a systemic inflammation of all tissues in the body, mainly localized in the pericardium. Especially the heart, joint and subcutaneous connective tissue in the body are prone to disease. Rheumatism can be caused by simple angina, which is common among people. Tonsillitis itself is acute, accompanied by fever, headache, and inflammation in rheumatic fever leads to chronic heart valve damage, which can lead to disability or death many years after the acute illness. can bring. Usually, rheumatism affects children between the ages of 5 and 15, but adults can also get sick. The first symptoms of rheumatism often begin to appear 1-5 weeks after angina. Rheumatic attacks usually last three months, rarely more than six months.